Grafted polyphenyl ether as well as preparation method and application thereof

By adding chain compounds and unsaturated acid anhydrides to the grafted chains of polyphenylene ether for modification, and combining it with supercritical foaming technology, high-performance grafted polyphenylene ether foam materials were prepared, which solved the shortcomings of polyphenylene ether materials in electrical and mechanical properties and enabled their application in high-end fields.

CN121673555APending Publication Date: 2026-03-17CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610089400.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-22
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing polyphenylene oxide materials have shortcomings in electrical and mechanical properties, making it difficult to meet the needs of high-end fields, especially the electrical performance and toughness requirements in 5G communication and high-frequency electronics.

Method used

By adding chain-like grafting compounds to the grafted chains of polyphenylene ether and chemically modifying it with unsaturated acid anhydrides and grafting aids, grafted polyphenylene ether can be prepared. Combined with supercritical foaming technology, the density and properties of the material can be controlled.

Benefits of technology

The prepared grafted polyphenylene ether foam material exhibits excellent performance in terms of density, mechanical properties, heat resistance, flame retardancy, and electrical properties, and is suitable for applications such as low-altitude aircraft, aerospace, and automotive materials, meeting diverse needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121673555A_ABST
    Figure CN121673555A_ABST
Patent Text Reader

Abstract

The present disclosure describes a grafted polyphenylene ether having a structure of formula I, a method for preparing the same, a composition for preparing the same, and a foam material and a method for preparing the foam material. The density of the grafted polyphenyl ether foaming material disclosed by the invention can be regulated and controlled in a range of 40-900 kg / m, and different requirements from an ultra-light heat insulation structure to a high-strength structure are met. The foaming material has excellent toughness and heat resistance, the elongation at break can reach 12.3%, the thermal deformation temperature is stabilized at 200 DEG C or above, and meanwhile, the inherent high flame retardant property (the oxygen index is larger than or equal to 30%) of polyphenyl ether is kept. (I)
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present disclosure relates to the technical field of polymer foam modification, and more specifically, to grafted polyphenylene ether, methods of making the same, compositions for making the same, and foamed materials and methods of making foamed materials. BACKGROUND

[0002] Polyphenylene ether (PPO) resin is a high-performance engineering plastic with excellent comprehensive performance, which has excellent mechanical strength, high heat distortion temperature (usually more than 200°C), inherent intrinsic flame retardancy (high oxygen index), extremely low dielectric constant and dielectric loss, and good hydrolysis resistance and chemical resistance. The polyphenylene ether foamed material prepared by taking polyphenylene ether resin as the matrix will inherit the many advantages of the intrinsic resin and has broad application prospects in the fields of aerospace, automobile transportation, integrated electronics, 5G communication, etc. SUMMARY

[0003] The inventors have surprisingly found that by grafting a chain grafting compound onto the grafting polyphenylene ether, the grafted polyphenylene ether prepared by the present application has excellent electrical and mechanical properties, and the density of the foamed material prepared therefrom can be regulated in the range of 40-900 kg / m³ to meet different requirements from ultra-light thermal insulation to high-strength structure. The foamed material has excellent toughness and heat resistance, with an elongation at break of up to 12.3%, a heat distortion temperature stable at more than 200°C, while maintaining the inherent high flame retardant properties of polyphenylene ether (oxygen index ≥ 30%). In addition, the foamed material also has excellent electrical properties, with a dielectric constant as low as 1.08 and a dielectric loss as low as 0.7 x 10 -3 , which is particularly suitable for high-end fields such as 5G communication and high-frequency electronics. The present application is obtained on the basis of the above unexpected discovery.

[0004] A conventional polyphenylene ether resin is used as raw material, and a one-step melt reaction processing method is used to chemically graft and modify the polyphenylene ether resin, directly improving the processability of the material, and preparing a grafted polyphenylene ether. The special material maximally maintains the heat resistance, flame retardance, strength, etc. of the polyphenylene ether resin.

[0005] Therefore, in a first aspect of the present disclosure, the present disclosure provides a grafted polyphenylene ether, which can have the structure of Formula I:

[0006] (I)

[0007] wherein R1and R2may each independently be selected from hydrogen and C 1-6 alkyl;

[0008] R3may be a C 11-39 hydrocarbon group, or a polysiloxane chain;

[0009] M + may be a metal ion;

[0010] x can be a variable introduced to make the whole of the grafted polyphenylene ether electrically neutral, for example x is 0, 1 or 2; and

[0011] n1 can be a ratio of ungrafted units, and n2 can be a ratio of grafted units, wherein n1 > 0, n2 > 0, and n1 + n2 = 100%.

[0012] In a second aspect of the present disclosure, the present disclosure provides a composition for preparing a grafted polyphenylene ether, for example the grafted polyphenylene ether is according to the first aspect, wherein the composition can comprise: a polyphenylene ether resin; an initiator; an unsaturated acid anhydride; a chain grafting compound; a grafting aid; and an antioxidant.

[0013] In a third aspect of the present disclosure, the present disclosure provides a method for preparing a grafted polyphenylene ether, which can comprise: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound, a grafting aid and an antioxidant, and reacting at 180 to 280 °C for 1.5 to 8 minutes to obtain a grafted polyphenylene ether, for example the grafted polyphenylene ether is according to the first aspect, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid and the antioxidant are the same as defined in the first aspect.

[0014] In a fourth aspect of the present disclosure, the present disclosure provides a method for preparing a grafted polyphenylene ether, which can comprise: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound and an antioxidant, and reacting at 180 to 280 °C for 1.5 to 5 minutes; then adding a grafting aid to the reaction system, and reacting for 0.5 to 3 minutes to obtain a grafted polyphenylene ether, for example the grafted polyphenylene ether is according to the first aspect, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid and the antioxidant are the same as defined in the first aspect.

[0015] In a fifth aspect of the present disclosure, the present disclosure provides a polyphenylene ether foamed material, which can be prepared by a foaming process using a grafted polyphenylene ether, wherein the grafted polyphenylene ether is according to the first aspect, or is prepared by the method according to the third aspect or the fourth aspect.

[0016] The present invention designs a unique reaction system, by introducing unsaturated anhydride, specific chain grafting compound and grafting aid containing metal ions into conventional polyphenyl ether resin, thereby realizing the regulation of the melt viscosity and rheological properties of polyphenyl ether, so as to meet the melt properties required for supercritical foaming. In addition, based on the above method, the present invention successfully prepares a grafted polyphenyl ether with high polyphenyl ether content (> 90%), which maximally maintains the heat resistance, flame retardance, strength and other properties of polyphenyl ether resin. The present invention further carries out supercritical physical foaming on the grafted polyphenyl ether, and obtains a polyphenyl ether foaming material (also referred to as "non-alloy type polyphenyl ether foaming material") with controllable foaming ratio. The polyphenyl ether foaming material shows significant advantages in density, mechanical property, heat resistance, flame retardance and electrical property, and can be applied in low-altitude aircraft, aerospace, automobile material, ship sandwich material, building material, thermal insulation material and other fields. BRIEF DESCRIPTION OF DRAWINGS

[0017] The accompanying drawings illustrate exemplary embodiments of the present disclosure and are used in conjunction with the foregoing description to provide a better understanding of the technical aspects of the present disclosure, and therefore, the present disclosure is not to be construed as being limited to the accompanying drawings.

[0018] Figure 1 A photograph of the foaming material of Example 1.

[0019] Figure 2 A photograph of the foaming material of Comparative Example 3.

[0020] Figure 3 A photograph of the foaming material of Comparative Example 4.

[0021] Figure 4 A photograph of the foaming material of Comparative Example 5. DETAILED DESCRIPTION

[0022] Hereinafter, the present disclosure will be described in more detail to help the understanding of the present disclosure.

[0023] It should be understood that the terms or words used in the specification and the appended claims should not be construed as being limited to the general and dictionary meanings and should be interpreted based on the meanings and concepts corresponding to the technical aspects of the present disclosure on the basis of the principle that the inventor is allowed to define the terms appropriately for the best explanation of the present disclosure.

[0024] It should be further understood that, unless otherwise explicitly specified, "comprise" or "include" as used in the specification indicates the presence of the stated elements and does not exclude the presence or addition of one or more other elements.

[0025] As used throughout, ranges are used as shorthand for describing each and every value and sub-range within the range. Any value within the range can be selected as the terminus of the range. Therefore, a range of 1 to 5 specifically includes 1, 2, 3, 4, and 5, as well as sub-ranges such as 2 to 5, 3 to 5, 2 to 3, 2 to 4, 1 to 4, etc.

[0026] As used herein, the term "selected from" means choosing one, two, or more from a candidate member.

[0027] As used herein, the term "C 1-6 "alkyl" means a straight-chain or branched-chain alkyl group having 1 to 6 carbon atoms, i.e. having 1, 2, 3, 4, 5, or 6 carbon atoms.

[0028] As used herein, the term "M + "means a metal ion, which can be monovalent, divalent, trivalent, or higher valent, preferably at least divalent, to achieve electroneutrality.

[0029] As used herein, the term "C 11-39 "hydrocarbyl" means a hydrocarbyl group having 11 to 39 carbon atoms, which can be a straight-chain or branched-chain, saturated or unsaturated hydrocarbyl group, preferably C 11 , C 13 , C 15 , C 17 , C 19 , C 21 , or C 23 hydrocarbyl group.

[0030] As used herein, the term "polysiloxane" means a polysiloxane having a molecular weight of between 500 and 5,000 Da, which can have a carboxyl or hydroxyl group at the end or side chain. For example, the end of the polysiloxane away from the metal ion is a carboxyl or hydroxyl, and can also be a carboxyl on the side chain of the polysiloxane.

[0031] As used herein, the term "carboxyl silicone oil" means a silicone oil in which a carboxyl group is introduced at one or both ends (i.e. end groups) of the polysiloxane molecular chain or on the side chain.

[0032] As used herein, the terms "ungrafted unit" and "grafted unit" mean unmodified and modified structural units, respectively.

[0033] As used herein, the term "polyphenylene ether resin" means a class of high molecular materials mainly composed of 2,6-dimethylphenol by polymerization, which contains repeating 2,6-dimethyl-1,4-phenylene ether units. In the present invention, the polyphenylene ether resin is the skeleton of the object to be modified and the final product.

[0034] As used herein, the term "grafted polyphenylene ether", also referred to as "non-alloyed polyphenylene ether" hereinafter, refers to a graft polymer formed with polyphenylene ether resin as the matrix, by grafting and ion-bridging reactions of unsaturated acid anhydride to introduce carboxyl-containing segments, which is a modified material specially designed and prepared to meet the specific requirements of supercritical physical foaming process.

[0035] As used herein, the term "unsaturated acid anhydride" refers to a compound containing at least one carbon-carbon double bond (C=C) and one acid anhydride group in the molecular structure. It is preferably an alkenyl-substituted five-membered ring acid anhydride, such as but not limited to maleic anhydride, itaconic anhydride, citraconic anhydride, 2-methyl maleic anhydride, and 2,3-dimethyl maleic anhydride, etc. These acid anhydrides can effectively graft onto the polyphenylene ether backbone due to their high reactivity of the double bond and the acid anhydride ring.

[0036] As used herein, the term "initiator" refers to a peroxide compound used to decompose and generate free radicals under melting conditions to initiate the grafting of unsaturated acid anhydride onto the polyphenylene ether molecular chain.

[0037] As used herein, the term "chain carboxylic acid" refers to a straight-chain or branched-chain carboxylic acid with a carbon atom number of 12 to 40.

[0038] As used herein, the term "chain grafting compound" refers to a chain molecule containing a carboxyl group, including a chain carboxylic acid or a carboxyl-modified polysiloxane (i.e., carboxyl silicone oil).

[0039] As used herein, the term "grafting aid" refers to a compound capable of providing metal ions of zinc, calcium, iron, barium, copper, nickel, etc. under the melting reaction conditions. It can be selected from salts, oxides or hydroxides containing the corresponding metal ions. For example, metal salts can directly provide metal ions; metal oxides or hydroxides can react with carboxylic acid components in the system to generate the corresponding metal carboxylate and release metal ions, thereby achieving the same technical effect.

[0040] As used herein, the term "antioxidant" refers to a class of additives that can delay or inhibit the aging degradation of materials due to oxidation. It is a key ingredient to ensure the stability of the performance and structure of the polymer during processing, storage and use.

[0041] As used herein, the term "supercritical physical foaming", also referred to as "supercritical foaming", is a process for preparing a foamed material using a fluid in a supercritical state as a physical foaming agent.

[0042] As used herein, the term "non-alloyed polyphenylene ether foamed material" refers to a foamed material made of grafted polyphenylene ether as the matrix by supercritical foaming process.

[0043] As used herein, the term "alloyed polyphenylene ether foam" refers to a foam made from polyphenylene ether blended with other polymers (such as polystyrene, nylon, etc.) after supercritical foaming process.

[0044] In a first aspect of the disclosure, the disclosure provides a grafted polyphenylene ether, which can have a structure of Formula I:

[0045] (I)

[0046] wherein R1and R2may each independently be selected from hydrogen and C 1-6 alkyl;

[0047] R3may be C 11-39 hydrocarbon group, or a polysiloxane chain;

[0048] M + may be a metal ion;

[0049] x can be a variable introduced to make the grafted polyphenylene ether as a whole electrically neutral, for example x is 0, 1 or 2; and

[0050] n1may be a percentage of ungrafted units, and n2may be a percentage of grafted units, wherein n1> 0, n2> 0, and n1+ n2= 100%. It is noted that this structure is a statistically representative schematic repeating unit structure of the grafted polyphenylene ether, rather than an exact molecular structure.

[0051] In some embodiments, non-limiting examples of R1and R2include methyl, ethyl, propyl, n-butyl, iso-butyl, sec-butyl, t-butyl, n-pentyl, iso-pentyl, neopentyl, n-hexyl, and the like. In some embodiments, R1or R2is methyl, ethyl, or propyl.

[0052] In some embodiments, n2 / (n1+ n2) is in the range of 0.01 to 2.5%, for example in the range of 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.32, 1.4, 1.5, 1.6, 1.8, 2, 2.2, 2.4 to 2.5%. In some embodiments, n2 / (n1+ n2) can be in the range of 0.03 to 1.5%. In some embodiments, n2 / (n1+ n2) can be in the range of 0.06 to 1.32%. In some embodiments, n2 / (n1+ n2) can be in the range of 0.15 to 1.32%. In some embodiments, n2 / (n1+ n2) can be in the range of 0.3 to 1%.

[0053] In some embodiments, R3may be C 11 , C 13 , C 15 , C 17 , C 19 , C 21 or C 23 hydrocarbyl; or a polysiloxane chain having a molecular weight of 500 to 5,000 Da. In some embodiments, the end of the polysiloxane chain distal to the metal ion is a carboxyl or hydroxyl group. In some embodiments, R3may be selected from linear or branched, saturated or unsaturated C 11、 C 12、 C 13、 C 14、 C 15、 C 16 or C 17 hydrocarbyl; or a carboxyl-modified polysiloxane chain having a molecular weight of 500 to 5,000 Da. In some embodiments, R3may be a mixture, which can be a mixture comprising hydrocarbyl and polysiloxane segments.

[0054] In some embodiments, M + may be selected from zinc ion, calcium ion, barium ion, copper ion, nickel ion, and iron ion. In some embodiments, M + may be in a valence state of one, two, three or higher, preferably at least two, to achieve electrical neutrality. The value of x can be determined by solving a charge balance equation based on the known and common oxidation states of the parts in the composition.

[0055] In some embodiments, the grafted polyphenylene ether is a grafted polymer network comprising: a polyphenylene ether backbone; carboxylate groups derived from an unsaturated anhydride grafted to the polyphenylene ether backbone via a covalent bond; chain-like carboxylic acid and / or carboxylic silicone units ionically linked to the carboxylate groups via metal cations; and metal cations ionically linked to the carboxylate groups, wherein the metal cations are derived from the grafting aid described above.

[0056] In a second aspect of the present disclosure, the present disclosure provides a composition for preparing a grafted polyphenylene ether, for example, the grafted polyphenylene ether is according to the first aspect, wherein the composition can comprise: a polyphenylene ether resin; an initiator; an unsaturated anhydride; a chain-like grafting compound; a grafting aid; and an antioxidant.

[0057] In some embodiments, the composition comprises 90 to 99 wt% of the polyphenylene ether resin, for example, 90, 91, 92, 93, 94, 95, 96, 97, 98 to 99 wt% of the polyphenylene ether resin, preferably 94 to 98.3 wt% of the polyphenylene ether resin, based on the total weight of the composition.

[0058] In some embodiments, the composition comprises 0.01 to 1 wt% of the initiator, for example 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8 to 1 wt% of the initiator, preferably 0.05 to 0.3 wt% of the initiator, based on the total weight of the composition.

[0059] In some embodiments, the composition comprises 0.03 to 3 wt% of the unsaturated acid anhydride, for example 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.4, 2.6, 2.8 to 3 wt% of the unsaturated acid anhydride, preferably 0.3 to 1 wt% of the unsaturated acid anhydride, based on the total weight of the composition.

[0060] In some embodiments, the composition comprises 0.5 to 5 wt% of the chain grafting compound, for example 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 to 5 wt% of the chain grafting compound, preferably 1 to 4 wt% of the chain grafting compound, based on the total weight of the composition.

[0061] In some embodiments, the composition comprises 0.1 to 2 wt% of the grafting aid, for example 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 to 2 wt% of the grafting aid, preferably 0.15 to 0.5 wt% of the grafting aid, based on the total weight of the composition.

[0062] In some embodiments, the composition comprises 0.1 to 0.5 wt% of the antioxidant, for example 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 to 0.5 wt% of the antioxidant, preferably 0.2 to 0.3 wt% of the antioxidant, based on the total weight of the composition.

[0063] In some embodiments, the composition can comprise 94 to 98.3 wt% of a polyphenylene ether resin; 0.05 to 0.3 wt% of an initiator; 0.3 to 1 wt% of an unsaturated anhydride; 1 to 4 wt% of a chain grafting compound; 0.15 to 0.5 wt% of a grafting aid; and 0.1 to 0.4 wt% of an antioxidant, wherein all weight percentages are based on the total weight of the composition.

[0064] In some embodiments, the polyphenylene ether resin can have a molecular weight (Mn) of 15,000 to 80,000 Da. In some embodiments, the polyphenylene ether resin can have a molecular weight (Mn) of 15,000, 16,000, 17,000, 18,000, 19,000, 20,000, 22,000, 24,000, 26,000, 28,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 76,000, 77,000, 78,000, to 80,000 Da.

[0065] In some embodiments, the unsaturated anhydride is a C 4-10 alkenyl dicarboxylic anhydride. In some embodiments, the unsaturated anhydride is specifically selected from maleic anhydride, itaconic anhydride, citraconic anhydride, 2-methyl maleic anhydride, and 2,3-dimethyl maleic anhydride.

[0066] In some embodiments, the initiator can be selected from cumene hydroperoxide (CHP), dicumyl peroxide (DCP), dibenzoyl peroxide (BPO), di-tert-butyl peroxide isopropyl benzene (BIPB), di-tert-butyl peroxide (DTBP), t-butyl peroxy neohexanoate (Lup701), diethylhexyl peroxydicarbonate (EHP), and t-butyl peroxy pivalate (BPP). Preferably, the initiator is selected from cumene hydroperoxide, dicumyl peroxide, di-tert-butyl peroxide isopropyl benzene, di-tert-butyl peroxide, and diethylhexyl peroxydicarbonate.

[0067] In some embodiments, the chain grafting compound is selected from a chain carboxylic acid and / or a carboxylic silicone oil. Preferably, the chain carboxylic acid is a C 12-24 carboxylic acid, preferably a C 12-18Fatty acid. The carboxyl silicone oil is a carboxyl terminated polydimethylsiloxane with a molecular weight of 500 to 5000 Da. In some embodiments, the carboxyl silicone oil is a carboxyl silicone oil with a molecular weight of 500, 600, 700, 800, 900, 1,000, 1,100, 1,200, 1,300, 1,400, 1,500, 1,600, 1,700, 1,800, 1,900, 2,000, 2,500, 3,000, 4,000 to 5,000 Da. Preferably, the carboxyl silicone oil is a di-terminated carboxyl silicone oil. More preferably, the carboxyl silicone oil is a di-terminated carboxyl silicone oil with a molecular weight of 1,000 to 2,000 Da. In some embodiments, the chain carboxylic acid can be selected from dodecanoic acid, tetradecanoic acid, hexadecanoic acid, and octadecanoic acid. In some embodiments, the carboxyl silicone oil can be a carboxyl silicone oil with a molecular weight of 500 Da, 1,000 Da, 2,000 Da, 3,000 Da, 4,000 Da, or 5,000 Da.

[0068] In some embodiments, the grafting aid is selected from metal organic or inorganic salts, metal oxides, or metal hydroxides containing one or more of zinc ions, calcium ions, barium ions, copper ions, nickel ions, and iron ions. In some embodiments, the grafting aid can be a metal organic or inorganic salt capable of providing metal ions or a metal oxide or metal hydroxide that can react with carboxylic acid to release metal ions. The metal ions include one or more of zinc ions, calcium ions, iron ions, barium ions, copper ions, nickel ions, or a mixture thereof. The metal organic or inorganic salt capable of providing metal ions is a mixture of one or more of formate, acetate, propionate, oxalate, carbonate, hydrochloride, sulfate, nitrate, phosphate salts containing the above metal ions (zinc ions, calcium ions, iron ions, barium ions, copper ions, nickel ions). The metal oxide or metal hydroxide that can react with carboxylic acid to release metal ions is a metal oxide and / or hydroxide containing one or more of zinc element, calcium element, iron element, barium element, copper element, nickel element. In some embodiments, preferably, the grafting aid is selected from zinc acetate, zinc oxide, zinc carbonate, calcium hydroxide, calcium carbonate, barium chloride, barium hydroxide, nickel nitrate, diiron trioxide, and nickel oxide.

[0069] In some embodiments, the antioxidant can be selected from the group consisting of antioxidant THP-EPQ (Tetrakis(2,4-di-tert-butylphenyl) 4,4'- biphenylenediphosphonite), antioxidant 1010 (Tetrakis[β-(3,5-di-tert-butyl-4- hydroxyphenyl)propionate]pentaerythritol), antioxidant 1076 (N-Octadecyl-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), antioxidant 168 (Tris(2,4-di-tert- butylphenyl) phosphite), antioxidant 626 (Bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite), antioxidant DLTP (Didodecylthiodipropionate), and antioxidant DSTP (Dioctadecylthiodipropionate). In some embodiments, the antioxidant can be selected from the group consisting of antioxidant THP-EPQ, antioxidant 1010, antioxidant 168, antioxidant 626, and antioxidant DLTP.

[0070] In a third aspect of the present disclosure, the present disclosure provides a method for preparing a grafted polyphenylene ether, which can comprise: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound, a grafting aid, and an antioxidant, and reacting at 180 to 280 °C for 1.5 to 8 minutes to obtain a grafted polyphenylene ether, for example, the grafted polyphenylene ether is the grafted polyphenylene ether according to the first aspect, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid, and the antioxidant are the same as defined in the first aspect.

[0071] In a fourth aspect of the present disclosure, the present disclosure provides a method for preparing a grafted polyphenylene ether, which can comprise: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound, and an antioxidant, and reacting at 180 to 280 °C for 1.5 to 5 minutes; then adding a grafting aid to the reaction system, and reacting for 0.5 to 3 minutes to obtain a grafted polyphenylene ether, for example, the grafted polyphenylene ether is the grafted polyphenylene ether according to the first aspect, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid, and the antioxidant are the same as defined in the first aspect.

[0072] In some embodiments, the method can further comprise processing the obtained grafted polyphenylene ether to obtain a grafted polyphenylene ether in the form of particles or plates.

[0073] In the embodiments of the present disclosure, a conventional polyphenyl ether with low price and wide raw material sources is used as a raw material, and the preparation of grafted polyphenyl ether is realized by a simple melt processing method through an in-situ reaction design scheme of "unsaturated acid anhydride grafting + ionic crosslinking". In addition, the method is simple and efficient, and is conducive to reducing the cost of the product. In the present disclosure, by controlling the feeding ratio of the chain grafting compound to be 0.5 to 5% based on the total weight of the composition, the melt characteristics of the grafted polyphenyl ether are adjusted so that it can be suitable for various foaming processes such as supercritical kettle foaming (bead foaming), supercritical mold foaming, supercritical foaming tank foaming, etc. If the feeding ratio of the chain grafting compound to the polyphenyl ether resin is too high, the final foam performance will be reduced; if the feeding ratio of the chain grafting compound to the polyphenyl ether resin is too low, the system viscosity will be too high, the melt processing will be difficult, and the foamability will be reduced.

[0074] In a fifth aspect of the present disclosure, the present disclosure provides a polyphenyl ether foaming material, which can be prepared by a foaming process using a grafted polyphenyl ether, wherein the grafted polyphenyl ether is the grafted polyphenyl ether according to the first aspect, or the grafted polyphenyl ether prepared by the method according to the third aspect or the fourth aspect.

[0075] In some embodiments, the method for preparing a non-alloyed polyphenyl ether supercritical physical foaming material can include the following steps: preparing the above-mentioned grafted polyphenyl ether into an intermediate body of a specified shape, preferably a plate with a thickness of 1 to 30 mm, and then placing the intermediate body in a foaming device for supercritical physical foaming. Specifically, the supercritical physical foaming can be carried out by using any one of the following two supercritical physical foaming methods: the supercritical physical foaming can be one-step foaming or two-step foaming.

[0076] The one-step foaming can include: placing the intermediate body into a supercritical foaming machine at a certain temperature, sealing the supercritical foaming machine; then introducing a physical foaming agent at a certain pressure; the intermediate body is saturated at the above-mentioned temperature and pressure for a certain time; then pressure relief foaming; quickly opening the supercritical foaming machine and taking out the foaming product to obtain a non-alloyed polyphenyl ether supercritical physical foaming material. For plate-shaped products that need to be flattened, flattening can be carried out on a flattening machine while hot. The above-mentioned supercritical foaming machine can be a kettle foaming machine, a mold foaming machine or a supercritical foaming tank. The physical foaming agent is one of CO2, N2 or a mixture of the two, the pressure is 4 to 25 MPa, the temperature is 200 to 240°C, the saturation time is 1 to 24 hours (the saturation time is mainly related to the thickness), and the average pressure relief rate is 1 to 10 MPa / s.

[0077] The two-step foaming process can include a high-pressure saturation stage and a low-pressure foaming stage. The high-pressure saturation stage can include placing the intermediate into a high-pressure saturation tank at a saturation temperature, closing the tank door, and then introducing a physical foaming agent at a saturation pressure, and performing permeation saturation in the high-pressure saturation tank for a certain saturation time. After saturation, the high-pressure saturation tank is depressurized and the permeation-saturated intermediate is removed; the permeation-saturated intermediate is placed into a low-pressure foaming tank and a physical foaming agent at a foaming pressure is introduced, and low-pressure foaming is performed at a foaming temperature for a controlled foaming time. After low-pressure foaming, the low-pressure foaming tank is opened and the foamed product is removed, and for samples that need to be leveled, the sample is leveled on a leveling machine while hot to obtain a non-alloyed polyphenyl ether supercritical physical foaming material. The process parameters of the two-step foaming process are: for the high-pressure saturation stage, the saturation temperature is 20 to 60 °C, the saturation pressure is 15 to 60 MPa, and the saturation time is 3 to 96 hours; for the low-pressure foaming stage, the foaming temperature is 200 to 240 °C, the foaming pressure is 2 to 10 MPa, and the foaming time is 0.5 to 4 hours. After the above permeation-saturated intermediate is removed from the high-pressure saturation tank, it can be placed in a low-pressure foaming tank for foaming, or it can be stored in an environment at normal pressure and 0 to 40 °C for 0 to 30 days, and then placed in a low-pressure foaming tank for foaming. Preferably, the storage time of the intermediate after being removed from the high-pressure saturation tank is ≤24 hours.

[0078] In some embodiments, the foamed material has a density of 40 to 900 kg / m3. In some embodiments, the foamed material has a density of 40 to 800 kg / m3. In some embodiments, the foamed material has a density of 40 to 600 kg / m3. In some embodiments, the foamed material has a density of 100 to 900 kg / m3.

[0079] In some embodiments, the foamed material has a heat distortion temperature ≥ 200 °C. In some embodiments, the foamed material has a heat distortion temperature ≥ 205 °C. In some embodiments, the foamed material has a heat distortion temperature ≥ 210 °C. In some embodiments, the foamed material has a heat distortion temperature ≥ 215 °C.

[0080] In some embodiments, the foamed material has an oxygen index ≥ 30%. In some embodiments, the foamed material has an oxygen index ≥ 32%. In some embodiments, the foamed material has an oxygen index ≥ 34%. In some embodiments, the foamed material has an oxygen index ≥ 36%.

[0081] In some embodiments, mixing can be performed using an internal mixer or an extruder. In some embodiments, the foamed material can be used in the fields of low-altitude aircraft, aerospace, automotive materials, ship sandwich materials, building materials, thermal insulation materials, etc.

[0082] Examples

[0083] Hereinafter, the effects and advantages of the present disclosure will be described in more detail through specific embodiments of the present disclosure. However, these embodiments are for illustrative purposes only, and the scope of the rights of the present disclosure is not determined thereby.

[0084] Example 1

[0085] 91.5 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., IV 30, molecular weight 15,000 Da), 0.3 wt% of CHP (cumene hydroperoxide), 2.5 wt% of maleic anhydride, 5 wt% of dodecanoic acid, and 0.2 wt% of antioxidant 1010 (pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) were thoroughly mixed, and the mixture was put into a banbury mixer at 240°C for melt mixing for 5 minutes. Then 0.5 wt% of zinc formate was added to the reaction system and melt mixing was continued for 3 minutes, and after discharging, pelletization was performed to obtain a grafted polyphenylene ether in the form of particles.

[0086] The obtained grafted polyphenylene ether was tabletized on a hot press at 260°C to make a plate-shaped intermediate with a thickness of 1 mm. The intermediate was put into a supercritical foaming machine mold at 240°C, the mold was closed, N2 was injected to a pressure of 25 MPa, and saturated for 1 hour. Subsequently, pressure relief foaming was performed at an average rate of 10 MPa / s. The mold was opened and the product was taken out to obtain a non-alloyed PPO (polyphenylene ether) foaming material. Figure 1 A photograph of the foaming material of Example 1.

[0087] Example 2

[0088] 99 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., IV 40, molecular weight 20,000 Da), 0.05 wt% of DCP (dicumene peroxide), 0.03 wt% of maleic anhydride, 0.5 wt% of carboxyl silicone oil with a molecular weight of 1,000 Da, 0.15 wt% of calcium propionate, and 0.27 wt% of antioxidant 1076 were thoroughly mixed, and the mixture was put into a twin-screw extruder for melt mixing processing. The eight partition temperatures of the twin-screw extruder were 180°C, 230°C, 270°C, 280°C, 280°C, 280°C, 275°C, and 270°C, respectively, with the die setting temperature being 270°C. The screw rotation speed was 200 r / min, and the material residence time was about 1.5 minutes, and then it was extruded and pelletized to obtain a grafted polyphenylene ether in the form of particles.

[0089] The obtained grafted PPO was extruded into a plate-shaped intermediate with a thickness of 30 mm by a plate extruder at 260°C. The intermediate was saturated with CO2 as a blowing agent in a supercritical foaming machine at 235°C and 25 MPa for 24 hours. Subsequently, the intermediate was foamed by rapid pressure release at a rate of 10 MPa / s. The foamed plate was hot-pressed in a calender at 215°C for 1 hour to obtain a non-alloyed PPO foamed material with a smooth surface.

[0090] Example 3

[0091] 96.3 wt% of polyphenylene ether resin (Xinbao New Material Technology Co., Ltd., molecular weight 80,000 Da), 0.3 wt% of BPO (dibenzoyl peroxide), 0.1 wt% of 2,3-dimethyl maleic anhydride, 2.6 wt% of tetracontanoic acid, 0.4 wt% of barium chloride, 0.3 wt% of antioxidant 168 (tris(2,4-di-tert-butylphenyl) phosphite) and antioxidant 1010 (3:4) were thoroughly mixed. The mixture was melt-mixed in a Banbury mixer at 260°C for 6 minutes, and then pelletized after discharging to obtain grafted PPO in the form of particles.

[0092] The obtained grafted PPO was pressed into a plate-shaped intermediate with a thickness of 1 mm on a hot press at 240°C. The intermediate was placed in a high-pressure saturation tank at 20°C, and a mixed gas of CO2 and N2 with a volume ratio of 3:7 was introduced to saturate the intermediate at 15 MPa for 3 hours. Subsequently, the pressure was released to atmospheric pressure at an average pressure release rate of 120 MPa / min. Then, the saturated intermediate was taken out and transferred to a low-pressure foaming tank at 200°C, and CO2 was introduced to a pressure of 2 MPa. After foaming for 0.5 hours, the pressure was released to atmospheric pressure at an average pressure release rate of 5 MPa / min to obtain a non-alloyed PPO foamed material.

[0093] Example 4

[0094] 98 wt% of polyphenylene ether resin (Xinbao New Material Technology Co., Ltd., molecular weight 50,000 Da), 0.1 wt% of BIPB (bis-tert-butyl peroxyisopropyl benzene), 0.4 wt% of maleic anhydride, 1.1 wt% of carboxyl silicone oil with a molecular weight of 5,000 Da, and 0.2 wt% of antioxidant 626 (bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite) were thoroughly mixed. The melt mixing process was carried out in a twin-screw extruder, and the temperatures of the eight zones of the twin-screw extruder were 180°C, 230°C, 275°C, 275°C, 280°C, 275°C, 275°C, and 270°C, respectively, with the die set temperature being 270°C. The screw rotation speed was 150 r / min. 0.2 wt% of copper sulfate was added through a side feeder at the 6th zone of the extruder. The residence time of the materials other than copper sulfate was about 2 minutes, and the residence time of copper sulfate in the screw was about 0.5 minutes. After the material was extruded, it was cut into particles with a diameter of about 1 mm to obtain the grafted polyphenylene ether in the form of particles.

[0095] The obtained grafted polyphenylene ether was placed in a batch supercritical physical foaming kettle, water was added as a heating medium, CO2 was introduced, the batch supercritical physical foaming kettle was heated to 200°C and the pressure in the kettle was maintained at 4 MPa, the stirring was started to make the intermediate suspended in the water, and the saturation time was 1 hour. Subsequently, the bottom discharge valve was opened, and the intermediate and water were discharged together at a rate of 1 MPa / s to obtain granular non-alloy PPO foam particles.

[0096] Example 5

[0097] 94.3 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 40,000 Da), 0.1 wt% of DTBP (di-tert-butyl peroxide), 0.1 wt% of Lup701 (tert-butyl peroxyneohexanoate), 1.5 wt% of 2-methyl maleic anhydride, 0.2 wt% of nickel oxide, 0.2 wt% of diiron trioxide, 3.4 wt% of carboxyl silicone oil with a molecular weight of 2,000 Da, 0.2 wt% of a mixture of antioxidants DLTP (dilauryl thiodipropionate) and DSTP (dioctadecyl thiodipropionate) (3:7) were thoroughly mixed. The melt mixing process was carried out in a twin-screw extruder, and the temperatures of the eight zones of the twin-screw extruder were 180°C, 230°C, 275°C, 275°C, 280°C, 275°C, 275°C, and 270°C, respectively, with the die set temperature being 270°C. The screw rotation speed was 150 r / min, and the residence time was about 2 minutes. After the material was extruded, it was cut into particles to obtain the grafted polyphenylene ether in the form of particles.

[0098] The grafted polyphenylene ether was extruded into a 20 mm thick plate-like intermediate at 265°C on a plate extrusion equipment. The intermediate was put into a high pressure saturation tank at 60°C, N2 was introduced, saturated at 60 MPa for 96 hours, then depressurized to normal pressure at 1.5 MPa / min. The saturated intermediate was then taken out. The saturated intermediate was placed in a normal pressure, 0°C environment for 30 days. Then it was put into a low pressure foaming tank at 240°C, a mixed gas of CO2 and N2 at a volume ratio of 1:1 was introduced to a pressure of 10 MPa. Foaming was carried out for 4 hours, then depressurized to normal pressure at an average depressurization rate of 40 MPa / min. The low pressure foaming tank was opened, and a non-alloyed PPO foamed material was obtained.

[0099] Example 6

[0100] 95.5 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 30,000 Da), 0.15 wt% of BPP (tert-butyl peroxy-2-ethylhexanoate), 2 wt% of citraconic anhydride, 1.2 wt% of octadecanoic acid, 0.7 wt% of carboxyl silicone oil with a molecular weight of 2,000 Da, 0.2 wt% of zinc carbonate, 0.05 wt% of barium hydroxide, and 0.2 wt% of a mixture (1:1) of antioxidant 1010 and antioxidant 168 were thoroughly mixed. Melt mixing processing was carried out in a twin-screw extruder, and the temperatures of the eight zones of the twin-screw extruder were set to 230°C, 250°C, 275°C, 275°C, 280°C, 275°C, 275°C, and 270°C, respectively, with the die temperature set to 270°C. The screw rotation speed was 250 r / min, and the residence time was about 1.5 min. The material was extruded and then pelletized to obtain grafted polyphenylene ether in the form of particles.

[0101] The grafted polyphenylene ether was pressed into a 10 mm thick plate-like intermediate at 280°C on a hot press. The intermediate was put into a high pressure saturation tank at 40°C, CO2 was introduced, saturated at 30 MPa for 24 hours, then depressurized to normal pressure at an average depressurization rate of 5 MPa / min, and the saturated intermediate was then taken out. The saturated intermediate was placed in a normal pressure, 25°C environment for 24 hours. Then it was put into a low pressure foaming tank at 230°C, CO2 was introduced to a pressure of 2 MPa, foaming was carried out for 2 hours, and then depressurized to normal pressure at an average depressurization rate of 20 MPa / min. The low pressure foaming tank was opened, and a non-alloyed PPO foamed material was obtained.

[0102] Example 7

[0103] 95 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 50,000 Da), 0.3 wt% of DCP, 1.8 wt% of maleic anhydride, 3.2 wt% of hexadecanoic acid, 0.5 wt% of zinc oxide and 0.2 wt% of antioxidant 168 were mixed well, melt-mixed in an internal mixer at 270°C for 5 minutes, taken out and cut into small pieces to obtain grafted polyphenylene ether; the grafted polyphenylene ether was pressed into a sheet on a hot press at 260°C to prepare an intermediate in the form of a 2 mm thick plate; the intermediate was placed in a supercritical foaming tank at 230°C, and a mixed gas of CO2 and N2 was introduced, with a mixing ratio of 7:3, a saturation pressure of 20 MPa, and a saturation time of 2 hours; the pressure in the supercritical foaming tank was then released to normal pressure at an average pressure release rate of 5 MPa / s, and the supercritical foaming tank was opened to obtain a non-alloyed PPO foaming material.

[0104] Example 8

[0105] 96 wt% of polyphenylene ether resin (Xinbao New Material Technology Co., Ltd., molecular weight 20,000 Da), 0.05 wt% of BPO, 0.15 wt% of DTBP, 1.2 wt% of maleic anhydride, 1.8 wt% of tetradecanoic acid and 0.2 wt% of antioxidant THP-EPQ were mixed well, melt-mixed in an internal mixer at 270°C for 3 minutes, then 0.4 wt% of zinc acetate was added and mixed for another 2 minutes, then taken out and cut into small pieces to obtain grafted polyphenylene ether in the form of a block.

[0106] The obtained grafted polyphenylene ether was pressed into a sheet on a hot press at 250°C to prepare a plate-shaped intermediate with a thickness of 4 mm; the intermediate was placed in a high-pressure saturation tank at 35°C, and a mixed gas of CO2 and N2 was introduced, with a mixing ratio of 5:5, a saturation pressure of 40 MPa, and a saturation time of 24 hours; the high-pressure saturation tank was then released to normal pressure at an average pressure release rate of 80 MPa / min, and the saturated intermediate was taken out and stored in an environment at 25°C for 1 day, then placed in a low-pressure foaming tank at 220°C, and N2 was introduced to a pressure of 4 MPa; the low-pressure foaming tank was foamed for 2 hours, then released to normal pressure at an average pressure release rate of 30 MPa / min, and the low-pressure foaming tank was opened to obtain a non-alloyed PPO foaming material.

[0107] Example 9

[0108] Example 1 95.2 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 30,000 Da), 0.2 wt% of DTBP, 1 wt% of 2-methyl maleic anhydride, 3.1 wt% of carboxyl silicone oil with a molecular weight of 4,000 Da, 0.2 wt% of calcium carbonate, 0.1 wt% of nickel nitrate, and 0.2 wt% of antioxidant DLTP were thoroughly mixed and melt-mixed in a twin-screw extruder. The eight partition temperatures of the twin-screw extruder were 180°C, 240°C, 265°C, 265°C, 270°C, 270°C, 270°C, and 265°C, respectively, with the die set temperature being 265°C. The screw rotation speed was 300 r / min, and the residence time of the material in the screw was about 1.5 min. After the material was extruded, it was cut into small particles with a diameter of about 2 mm to obtain the grafted polyphenylene ether in the form of particles.

[0109] The obtained grafted polyphenylene ether was pressed into a 10 mm plate-shaped intermediate on a hot press at 280°C. The intermediate was placed in a supercritical CO2 foaming machine for foaming. The specific foaming process parameters were: foaming temperature 240°C, saturation pressure 10 MPa, and foaming time 10 hours. Subsequently, the foaming was rapidly released at a rate of 8 MPa / s, and then flattened by a flattening machine at 225°C for 1 hour to obtain the non-alloyed PPO foaming material.

[0110] Example 10

[0111] 97.5 wt% of polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 30,000 Da), 0.1 wt% of DCP, 0.4 wt% of maleic anhydride, 1.5 wt% of carboxyl silicone oil with a molecular weight of 3,000 Da, and 0.2 wt% of antioxidant 626 were thoroughly mixed and melt-mixed in a twin-screw extruder. The eight partition temperatures of the twin-screw extruder were 220°C, 250°C, 270°C, 270°C, 280°C, 280°C, 280°C, and 270°C, respectively, with the die set temperature being 270°C. 0.2 wt% of calcium hydroxide and 0.1 wt% of barium hydroxide were fed into the extruder at the 6th zone of the screw. The screw rotation speed was 250 r / min, and the residence time of the material in the screw was about 1.5 min, except for calcium hydroxide and barium hydroxide, which had a residence time of about 0.5 min in the screw. After the material was extruded, it was cut into small particles with a diameter of about 1.5 mm to obtain the grafted polyphenylene ether in the form of particles.

[0112] The obtained grafted PPO was extruded into a plate-shaped intermediate with a thickness of 8 mm at 270°C on a plate extrusion device. The intermediate was put into a supercritical foaming tank at 235°C, N2was introduced into the tank to a pressure of 25 MPa, and saturated penetration was carried out for 16 hours in this state. Then, the pressure in the supercritical foaming tank was released to normal pressure at an average pressure release rate of 8 MPa / s, the supercritical foaming tank was opened, the foamed plate was taken out, and the foamed plate was leveled by a leveling machine at 230°C for 1.5 hours to obtain a non-alloyed PPO foamed material.

[0113] Example 11

[0114] A mixture of 95.55 wt% of a polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 30,000 Da), 0.15 wt% of BPO, 0.6 wt% of itaconic anhydride, 3.0 wt% of octadecanoic acid, 0.5 wt% of copper phosphate, and 0.2 wt% of antioxidant Lup 701 was thoroughly mixed, melt-mixed in a Banbury mixer at 280°C for 6 minutes to obtain grafted PPO, which was taken out and cut into small pieces. The grafted PPO in pieces was pressed into a plate-shaped intermediate with a thickness of 3 mm on a hot press at 250°C. The intermediate was put into a high-pressure saturation tank at 40°C, mixed gas of CO2and N2with a mixing ratio of 9:1 was introduced into the tank, the saturation pressure was 20 MPa, and saturation was carried out for 10 hours. Then, the high-pressure saturation tank was released to normal pressure at an average pressure release rate of 60 MPa / min, the saturated intermediate was taken out and put into a low-pressure foaming tank at 215°C, N2was introduced into the tank to a pressure of 3 MPa, and foaming was carried out for 1 hour. Then, the pressure in the low-pressure foaming tank was released to normal pressure at an average pressure release rate of 20 MPa / min, the low-pressure foaming tank was opened, and a non-alloyed PPO foamed material was obtained.

[0115] Example 12

[0116] A mixture of 96.5 wt% polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., molecular weight 30,000 Da), 0.3 wt% EHOD, 0.8% citraconic anhydride, 1.9 wt% carboxyl silicone oil with a molecular weight of 500 Da, 0.2 wt% iron oxide, 0.1 wt% nickel oxide, and 0.2 wt% antioxidant 626 was mixed thoroughly and melt-mixed in a twin-screw extruder, with the eight-zone temperatures of the twin-screw extruder being 220°C, 230°C, 255°C, 260°C, 260°C, 260°C, 260°C, and 260°C, respectively, and the die temperature being set to 260°C. The screw rotation speed was 260 r / min, and the residence time of the material in the screw was about 1.5 min. Grafted polyphenylene ether was obtained. After extrusion, it was cut into small particles with a diameter of about 2 mm and pressed into a 5-mm-thick plate intermediate on a hot press at 270°C. The intermediate was placed in a CO2 supercritical foaming machine for foaming, with the foaming process parameters being a foaming temperature of 230°C, a saturation pressure of 15 MPa, and a foaming time of 6 h. Rapid pressure relief foaming was performed at 6 MPa / s to obtain a non-alloyed PPO foaming material.

[0117] Comparative Example 1

[0118] A mixture of 50 wt% polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., IV 30, molecular weight 15,000 Da), 45 wt% high-impact polystyrene (HIPS) (Zhenjiang Qimei Chemical Co., Ltd., PH-888G), 4.8 wt% styrene-maleic anhydride copolymer (PS-G-MA) (Shanghai Xintin New Material Co., Ltd., MA content 1.5%), and 0.2 wt% antioxidant 1010 was mixed thoroughly and placed in a 200°C internal mixer for melt mixing for 8 min. After discharging, the particles were obtained to obtain an alloyed polyphenylene ether foaming material.

[0119] The alloyed polyphenylene ether foaming material was pressed into a plate-shaped intermediate with a thickness of 1 mm on a hot press at 180°C. The intermediate was placed in a mold of a mold foaming machine at 120°C, the mold was closed, nitrogen (N2) was injected to a pressure of 25 MPa, and was saturated for 1 h. Subsequently, pressure relief foaming was performed at an average rate of 10 MPa / s. The mold was opened and the product was taken out to obtain an alloyed PPO foam.

[0120] Comparative Example 2

[0121] A mixture of 92.9 wt% of a hydroxyl-terminated polyphenylene ether resin (SABIC, SA90, molecular weight 2,000 Da), 0.3 wt% of antioxidant THP-EPQ, 0.5 wt% of silicone powder, 0.8 wt% of potassium carbonate was mixed thoroughly. The mixed material was fed into the feeding port of a twin-screw extruder, and then 5.5 wt% of diphenyl phosphate acid chloride was fed from the side feeding port. Twin-screw extrusion was performed with the temperature of 9 zones of the twin-screw extruder being 180°C, 220°C, 250°C, 265°C, 270°C, 270°C, 270°C, 270°C, and 270°C, respectively, and the die set temperature being 275°C. The screw rotation speed was 150 r / min. The mixed material was melt plasticized, kneaded, fully reacted and grafted, extruded, cooled, cut, and made into a PPO plate intermediate with a thickness of 5 mm. The intermediate was saturated with CO2 as the foaming agent in a supercritical foaming machine at 180°C and 18 MPa for 3 hours, then depressurized at a rate of 7 MPa / s, and leveled with a leveling machine at 150°C for 1 hour to obtain a flame-retardant (non-alloy type) PPO foam plate with a smooth surface.

[0122] Comparative Example 3

[0123] A mixture of 93 wt% of a polyphenylene ether resin (Nantong Xingchen Synthetic Material Co., Ltd., IV30, molecular weight 15,000 Da), 0.3 wt% of CHP, 1 wt% of maleic anhydride, 6 wt% of dodecanoic acid, and 0.2 wt% of antioxidant 1010 was mixed thoroughly, melt mixed in a Banbury mixer at 240°C for 5 minutes, then 0.5 wt% of zinc formate was added, and melt mixed for another 3 minutes to obtain grafted polyphenylene ether, which was taken out and cut into small pieces. The cut grafted polyphenylene ether was pressed into a plate-shaped intermediate with a thickness of 1 mm on a hot press at 260°C. The intermediate was placed in a supercritical foaming machine mold at 240°C, the mold was closed, N2 was introduced to a pressure of 25 MPa, and saturated for 1 hour. Then, the pressure was released to foam at an average pressure release rate of 10 MPa / s; the mold was opened to obtain a non-alloy type PPO foaming material.

[0124] Comparative Example 4

[0125] 98.3% by weight of polyphenylene ether resin (Nantong Xingchen Synthetic Materials Co., Ltd., IV40, molecular weight 20,000 Da), 0.05% by weight of DCP, 0.3% by weight of maleic anhydride, 0.4% by weight of carboxylated silicone oil with a molecular weight of 1,000 Da, 0.15% by weight of calcium propionate, and 0.2% by weight of antioxidant 1076 were thoroughly mixed and melt-mixed in a twin-screw extruder. The eight zones of the twin-screw extruder were set to temperatures of 180°C, 230°C, 270°C, 280°C, 280°C, 275°C, and 270°C, with the die head set at 270°C. The screw speed was 150 r / min, and the material residence time in the screw was approximately 1.5 minutes. After extrusion, the material was pelletized to obtain granular grafted polyphenylene ether. The grafted polyphenylene ether was pressed into a 2 mm thick plate-like intermediate at 260°C using a hot press. The intermediate was then placed in a supercritical CO2 foaming machine for foaming. The specific foaming parameters were: foaming temperature 235°C, saturation pressure 25 MPa, foaming time 2 hours, followed by rapid depressurization at 10 MPa / second. The foam density was 320 kg / m³. 3 Heat distortion temperature 215°C.

[0126] Comparative Example 5

[0127] 97% by weight of polyphenylene ether resin (Nantong Xingchen Synthetic Materials Co., Ltd., IV40, molecular weight 20,000 Da), 0.3% by weight of DCP, 2.5% by weight of maleic anhydride, and 0.2% by weight of antioxidant 1010 were thoroughly mixed at 280°C. o PPO-grafted maleic anhydride was obtained by melting and processing in a C-type internal mixer for 5 minutes. The PPO-grafted maleic anhydride was then pressed into a 3 mm thick plate-shaped intermediate at 260°C on a hot press. The intermediate was then placed in a CO2 supercritical foaming machine for foaming. The specific foaming process parameters were: foaming temperature of 240°C, saturation pressure of 20 MPa, foaming time of 4 hours, followed by rapid depressurization and foaming at 10 MPa / second.

[0128] like Figure 2 As shown, the foam in Comparative Example 3 exhibited melting, cell collapse, and irregular bubbling. Figure 3 As shown, the foam of Comparative Example 4 exhibited obvious defects, a rough surface with holes, and internal cavities and cracks. Comparative Examples 3 and 4 demonstrate that if the proportion of the chain-like grafted compound is too high or too low, the foaming performance of the grafted polyphenylene ether decreases, thus hindering the acquisition of stable and high-quality PPO foam products.

[0129] like Figure 4As shown, the sample of Comparative Example 5 after mold opening shows that internal bubbles were generated, but there are a lot of cracks and bubbling phenomena in the sample, making it difficult to measure density and various mechanical properties.

[0130] The performance of the foamed materials obtained in Examples 1 to 10 and Comparative Examples 1 to 4 was tested, and the results are shown in Table 1 below.

[0131]

[0132] The non-alloy grafted polyphenylene ether and its foamed materials provided in this application exhibit significant advantages in density, mechanical properties, heat resistance, flame retardancy, and electrical properties. Specifically, the density of the foamed materials of this invention can range from 40 to 900 kg / m³, meeting different needs from ultra-lightweight insulation to high-strength structures. At similar or lower densities, the mechanical properties of the foamed materials of this invention are superior: for example, the compressive and tensile strength of Example 1 (40 kg / m³) is comparable to that of the higher-density alloy-type Comparative Example 1 (52 kg / m³), and the elongation at break of Examples 1 to 10 (7.6%-12.3%) is much higher than that of the Comparative Example (3.6%-4.2%), indicating a fundamental improvement in impact resistance; the flexural strength (2.7 MPa) of Example 2 (68 kg / m³) is also higher than that of the higher-density Comparative Example 2 (92 kg / m³, 2.2 MPa). Regarding heat resistance, the heat distortion temperature of all embodiments consistently exceeded 200°C, significantly superior to Comparative Example 1 (124°C) and Comparative Example 2 (150°C). Furthermore, the foamed materials of this invention all possess high oxygen indexes (30%-38%), inheriting the excellent flame retardancy of the PPO bulk. In terms of electrical properties, this material exhibits low dielectric constant and dielectric loss in the low-density range, superior to Comparative Example 1 and Comparative Example 2, making it suitable for applications such as high-frequency communications.

[0133] Although several embodiments of this disclosure have been described and illustrated herein, those skilled in the art will readily contemplate a variety of other ways and / or structures for performing the functions described herein and / or obtaining the results described herein and / or one or more advantages, and each such variation and / or modification is considered to be within the scope of this disclosure.

Claims

1. A grafted polyphenylene ether having a structure of Formula I: (I) wherein R1and R2are each independently selected from the group consisting of hydrogen and C 1-6 alkyl; R3is C 11-39 hydrocarbon group, or a polysiloxane chain; M + is a metal ion; x is a variable introduced to make the grafted polyphenylene ether as a whole electrically neutral, for example x is 0, 1, or 2; and n1 is a non-grafted unit fraction, n2 is a grafted unit fraction, wherein n1 > 0, n2 > 0, and n1 + n2 = 100%.

2. The grafted polyphenylene ether of claim 1, wherein R3 is C 11 , C 13 , C 15 , C 17 , C 19 , C 21 or C 23 hydrocarbyl; or a polysiloxane chain having a molecular weight of 500 to 5,000 Da, for example the terminal end of the polysiloxane chain that is distal from the metal ion is a carboxyl or hydroxyl group.

3. A composition for preparing a grafted polyphenylene ether, wherein the composition comprises: a polyphenylene ether resin; an initiator; an unsaturated acid anhydride; a chain grafting compound; a grafting aid; and an antioxidant.

4. The composition of claim 3, wherein the composition comprises 90 to 99 weight % of the polyphenylene ether resin, for example 90, 91, 92, 93, 94, 95, 96, 97, 98 to 99 weight % of the polyphenylene ether resin, preferably 94 to 98.3 weight % of the polyphenylene ether resin, based on the total weight of the composition.

5. The composition of claim 3 or 4, wherein the composition comprises 0.01 to 1 weight % of the initiator, for example 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8 to 1 weight % of the initiator, preferably 0.05 to 0.3 weight % of initiator, based on the total weight of the composition.

6. The composition of any one of claims 3 to 5, wherein the composition comprises 0.03 to 3 weight % of the unsaturated acid anhydride, for example 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.4, 2.6, 2.8 to 3 weight % of the unsaturated acid anhydride; preferably 0.3 to 1 weight % of the unsaturated acid anhydride, based on the total weight of the composition.

7. The composition of any one of claims 3 to 6, wherein the composition comprises 0.5 to 5 weight % of the chain grafting compound, for example 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 to 5 weight % of the chain grafting compound, preferably 1 to 4 weight % of the chain grafting compound, based on the total weight of the composition.

8. The composition according to any one of claims 3 to 7, wherein the composition comprises 0.1 to 2 wt% of the grafting aid, for example 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.4, 1.6, 1.8 to 2 wt% of the grafting aid, preferably 0.15 to 0.5 wt% of the grafting aid, based on the total weight of the composition.

9. The composition according to any one of claims 3 to 8, wherein the composition comprises 0.1 to 0.5 wt% of the antioxidant, for example 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 to 0.5 wt% of the antioxidant, preferably 0.2 to 0.3 wt% of the antioxidant, based on the total weight of the composition.

10. The composition according to any one of claims 3 to 9, wherein the chain grafting compound is selected from a chain carboxylic acid and / or a carboxy silicone oil; preferably, the chain carboxylic acid is a C 12-24 carboxylic acid, preferably a C 12-18 fatty acid; and the carboxy silicone oil is a carboxy terminated polydimethylsiloxane having a molecular weight of 500 to 5,000 Da, preferably the carboxy silicone oil is a di-terminated carboxy silicone oil, more preferably the carboxy silicone oil is a di-terminated carboxy silicone oil having a molecular weight of 1,000 to 2,000 Da.

11. The composition according to any one of claims 3 to 10, wherein the grafting aid is selected from metal organic or inorganic salts, metal oxides or metal hydroxides containing one or more of zinc ions, calcium ions, barium ions, copper ions, nickel ions and iron ions; preferably, the grafting aid is selected from zinc acetate, zinc oxide, zinc carbonate, calcium hydroxide, calcium carbonate, barium chloride, barium hydroxide, nickel nitrate, diiron trioxide and nickel oxide.

12. A method for preparing a grafted polyphenylene ether, comprising: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound, a grafting aid and an antioxidant, and performing a reaction at 180 to 280 °C for 1.5 to 8 minutes to obtain a grafted polyphenylene ether, for example the grafted polyphenylene ether is the grafted polyphenylene ether according to claim 1 or 2, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid and the antioxidant are the same as defined in claims 3 to 11.

13. A method for preparing a grafted polyphenylene ether, comprising: mixing a polyphenylene ether resin, an initiator, an unsaturated acid anhydride, a chain grafting compound and an antioxidant, and performing a reaction at 180 to 280 °C for 1.5 to 5 minutes; then adding a grafting aid to the reaction system, and performing a reaction for 0.5 to 3 minutes to obtain a grafted polyphenylene ether, for example the grafted polyphenylene ether is the grafted polyphenylene ether according to claim 1 or 2, wherein the polyphenylene ether resin, the initiator, the unsaturated acid anhydride, the chain grafting compound, the grafting aid and the antioxidant are the same as defined in claims 3 to 11.

14. A polyphenylene ether foamed material prepared by a foaming process using a grafted polyphenylene ether, wherein the grafted polyphenylene ether is the grafted polyphenylene ether according to claim 1 or 2, or prepared by the method according to claim 12 or 13.